2016
DOI: 10.2174/1874325001610010364
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Soft Tissue Reconstruction Algorithm in Patients With Open Tibia Fractures

Abstract: Introduction:Tactic of emergency closing of soft tissue defect allows to significantly improve the treatment results concerning patients with severe open fractures. However, a number of certain factors make the implementation of this tactic rather difficult. Injured people’s unstable conditions are mong these crucial factors which include, polytrauma in lots of cases, absence of exact recommendations for recovery terms, choice of definite tissue flaps and a type of circulation.The Aim of Study:is to develop ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(29 reference statements)
2
7
0
Order By: Relevance
“…However, the proportion of complications increased with age. Our finding is comparable with the findings of the study conducted by Ivanov et al [ 5 ], in which the majority of the cases were in the age range of 31–45 years (35%), followed by the age groups of 18–30, 46–60, and > 60 years, which accounted for 34%, 20%, and 7% of cases, respectively. However, a systematic review by de Blacam et al [ 2 ] correlated sural flap complications with predisposing factors and reported that age and venous insufficiency were independent risk factors for flap and wound complications.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the proportion of complications increased with age. Our finding is comparable with the findings of the study conducted by Ivanov et al [ 5 ], in which the majority of the cases were in the age range of 31–45 years (35%), followed by the age groups of 18–30, 46–60, and > 60 years, which accounted for 34%, 20%, and 7% of cases, respectively. However, a systematic review by de Blacam et al [ 2 ] correlated sural flap complications with predisposing factors and reported that age and venous insufficiency were independent risk factors for flap and wound complications.…”
Section: Discussionsupporting
confidence: 92%
“…No statistically significant correlation was found between sex and complications. In the study by Ivanov et al [5], 15 cases (17.6%) were female and 70 (82.4%) cases were male, which is a comparable ratio to that of our study. In the study conducted by Chua et al [9], 6.74% of the patients were female patients and 93.36% were male.…”
Section: Sex and Flap Complicationssupporting
confidence: 89%
“…Reconstructive algorithms for complex extremity injuries have been described with potential benefits in patient outcomes. 30 Based upon the above characterization of extremity DSTIs and the factors affecting their outcomes, we propose an extremity DSTI classification and management algorithm. Although we understand there are nuances to the management of DSTIs of different anatomic locations, the proposed classification system simplifies the injuries into 2 groups based upon the anatomic level of injured tissues, which is generalizable to various anatomic levels due to the presence of fascial structures in both the upper and lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…This reduced the time to union and the incidence of infection 35,36,37 . It should be emphasised that timing of early soft tissue reconstruction is still debatable with some studies advocating coverage within three to five days of injury 29,34,37,38,39 and others favouring immediate wound cover at the time of initial surgery 21,40 . Our five-year study supported the observation that if the patient were hemodynamically stable, delay in soft tissue cover was unnecessary, as it could lead to additional soft tissue loss and a further increase in chances of wound contamination.…”
Section: Discussionmentioning
confidence: 99%